Bacterial metabolism in the host and its association with virulence - Amrita Bhagwat; Tiyasa Haldar; Poonam Kanojiya; Sunil D. Saroj (Virulence)
The host restricted pathogens are competently dependent on their respective host for nutritional requirements. The bacterial metabolic pathways are surprisingly varied and remarkably flexible that in turn help them to successfully overcome competition and colonise their host. The metabolic adaptation plays pivotal role in bacterial pathogenesis. The understanding of host-pathogen metabolic crosstalk needs to be prioritized to decipher host-pathogen interactions. The review focuses on various aspects of host pathogen interactions that majorly involves adaptation of bacterial metabolism to counteract immune mechanisms by rectifying metabolic cues that provides pathogen the idea of different anatomical sites and the local physiology of the host. The key set of metabolites that are recognized as centre of competition between host and its pathogens are also briefly discussed. The factors that control the timely expression of virulence of bacterial pathogens is poorly understood. The perspective presented herein will facilitate us with a broader view of molecular mechanisms that modulates the expression of virulence factors in bacterial pathogens. The knowledge of crosslinked metabolic pathways of bacteria and their host will serve to develop novel potential therapeutics.